2001
DOI: 10.1051/0004-6361:20010628
|View full text |Cite
|
Sign up to set email alerts
|

Argon, silicon and iron abundances in the damped Ly-αsystem I Zw 18

Abstract: Abstract. We show how the ratio of the abundances of Ar, Si and Fe as derived from FUSE absorption spectra of I Zw 18 are affected by large-scale stochastic velocity fields (mesoturbulence). 21-cm observations with high spatial resolution show the presence of velocity fields with large correlation lengths. FUSE observations were performed with a large entrance aperture which fully covered the galaxy. This means that the observed profiles are averaged over the full body of I Zw 18. Taking this into account, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 34 publications
2
48
0
Order By: Relevance
“…Results by Pettini & Lipman (1995) and van Zee et al (1998) seem to indicate indeed a metallicity comparable to the abundance in the H ii regions. A recent work of Levshakov et al (2001) about argon and silicon emission line profiles in IZw18 also reveals a good degree of mixing between hot and cold regions. Future FUSE abundance determinations will certainly shed more light on the problem.…”
Section: Izw18mentioning
confidence: 74%
See 2 more Smart Citations
“…Results by Pettini & Lipman (1995) and van Zee et al (1998) seem to indicate indeed a metallicity comparable to the abundance in the H ii regions. A recent work of Levshakov et al (2001) about argon and silicon emission line profiles in IZw18 also reveals a good degree of mixing between hot and cold regions. Future FUSE abundance determinations will certainly shed more light on the problem.…”
Section: Izw18mentioning
confidence: 74%
“…Recently, Levshakov et al (2001) with their mesoturbulent approach, found higher overabundances of α elements (they found [Si, Ar/Fe] = 0.7 ± 0.1). Since there are some indications that the WW yields of iron are overestimated by a factor of 2 (Timmes et al 1995), we tried to calculate α/Fe ratios with reduced iron yields from massive stars and the results for [Mg/Fe] and [Si/Fe] evolution are shown in Fig.…”
Section: Chemical Evolution Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…established that these authors overestimated the solar oxygen composition (Holweger 2001). We keep this value since, due to the difficulties in the estimation of the iron content in IZw18 (see e.g., Izotov et al 1997b;Levshakov et al 2001) …”
Section: Chemical Evolutionmentioning
confidence: 99%
“…Since these systems arise in gas ejected from the circumnuclear region, careful analysis of the element abundances can produce important clues about the enrichment mechanisms and physical processes leading to the QSO/AGN phenomena. The numbers presented in Table 1 are obtained with the Monte Carlo Inversion (MCI) method -an advanced computational procedure designed to estimate the physical parameters of optically thin absorbers with varying gas density and turbulent velocity field (Levshakov et al 2000).We conclude the following:• The analyzed absorption systems show high iron content, [Fe/C] = 0.15 ± 0.1, [Fe/Mg] = 0.0 ± 0.1 (z abs =1.78), but at the same time nitrogen is strongly underabundant, [N/C] < ∼ −0.5 (z abs =1.68). These abundances are estimated in different associated systems but they are representative for the bulk of circumnuclear gas since the mass of the stellar population involved in the enrichment of quasar's circumnuclear region is high, > 10 4 M , (Baldwin et al 2003) and, hence, large metallicity gradients and sharp discontinuities due to enrichment by only a few stars are unlikely.…”
mentioning
confidence: 99%